Team Social Media Usage and Team Creativity: The Role of Team Knowledge Sharing and Team-Member Exchange - Wang, Hui; Xiao, Yuting; Su, Xinwen; Li, Xiangqing (Frontiers in Psychology, 2021)
Given that work teams have been widely used in a variety of organizations to complete critical tasks and that the use of social media in work teams has been growing, investigating whether and how team social media usage (TSMU) affects team creativity is imperative. However, little research has empirically explored how TSMU affects team creativity. This study divides TSMU into two categories, namely, work-related TSMU and relationship-related TSMU. Basing on communication visibility theory and social exchange theory, this study constructs a moderating mediation model to understand how TSMU affects team creativity. In this model, team knowledge sharing is used as mediating role and team-member exchange (TMX) is used as moderating role. Two-wave research data collected from 641 employees in 102 work teams in Chinese organizations are used for regression analysis. Results show that (1) Work-related TSMU and relationship-related TSMU are positively affect team creativity. (2) Team knowledge sharing plays a partly mediating effect on the relationship between work-related TSMU and team creativity and that between relationship-related TSMU and team creativity. (3) TMX not only positively moderates the indirect effect of work-related TSMU and relationship-related TSMU on team creativity through team knowledge sharing. Theoretical and practical implications are also discussed.